Clinical potential of stem cells - Martin, John (Henry Stewart Talks, 2007)
Amphibians and organ repair, Application of different cell types to the heart in animal models, Stem cell repair is complex, The mechanism of efficacy is unknown, Intellectual property in autologous stem cells, Autologous bone marrow cells can cause an increase in ejection fraction after myocardial infarction, Definitive randomised, controlled, blinded trials are needed, Gene therapy plus stem cell therapy is the future